2012
DOI: 10.1007/s11524-012-9747-x
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use and Concurrent Partnering among Heterosexually Active, African American Men: A Qualitative Report

Abstract: African Americans are overrepresented among heterosexual cases of HIV/ AIDS in the USA. Inconsistent condom use and concurrent partnering are two sexual behaviors driving the heterosexual HIV epidemic in the African American community. To inform the development of an HIV prevention behavioral intervention to decrease concurrent partnering and increase condom use among African American heterosexual men, we conducted formative research, including 61 structured interviews, 5 focus groups with 25 men, and 30 in-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…HIV testing is critical in order to reduce the risk of transmission, and awareness of HIV serostatus is a strong determinant of condom use and sexual partnering patterns (Ebrahim, Anderson, Weidle, & Purcell, 2004), yet little is known about HIV testing behaviors among heterosexual African-American men (Marks, Crepaz, & Janssen, 2006). As part of a CDC-funded study designed to develop and test an HIV prevention intervention for African-American heterosexual men, we conducted a formative research study using mixed methods (Frye et al, 2012). Here, we adopt a social cognitive perspective to inform an analysis of how heterosexual African- American men make sense of HIV testing, the influence of their female partners on HIV testing, and the impact of communication about HIV testing in heterosexual relationships.…”
mentioning
confidence: 99%
“…HIV testing is critical in order to reduce the risk of transmission, and awareness of HIV serostatus is a strong determinant of condom use and sexual partnering patterns (Ebrahim, Anderson, Weidle, & Purcell, 2004), yet little is known about HIV testing behaviors among heterosexual African-American men (Marks, Crepaz, & Janssen, 2006). As part of a CDC-funded study designed to develop and test an HIV prevention intervention for African-American heterosexual men, we conducted a formative research study using mixed methods (Frye et al, 2012). Here, we adopt a social cognitive perspective to inform an analysis of how heterosexual African- American men make sense of HIV testing, the influence of their female partners on HIV testing, and the impact of communication about HIV testing in heterosexual relationships.…”
mentioning
confidence: 99%
“…This may be due to general dislike of condoms as well as the perception that the individual who proposes condom use within a partnership will be perceived as the unfaithful one (13). …”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies among African American adults suggest that while concurrency is normative in some circumstances, many report a committed monogamous relationship as the ideal (13, 14). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that emotional connections, particularly those in monogamous, committed relationships, may decrease some Black women’s perceptions of risk and willingness to use condoms (Epperson et al, 2009; Kyomugisha, 2006). Lastly, scholars have found that older Black women may be at risk for HIV, particularly when married or in committed relationships in which they do not use condoms because pregnancy prevention and sexual concurrency, or having overlapping sexual partnerships, are not major concerns for them (Frye et al, 2013; Smith & Larson, 2015). …”
mentioning
confidence: 99%